Hydra Supercluster of Galaxies: photometric Investigation and Galaxy-Cluster Memberships - Lösch, Elismar (2024)
At scales of dozens of Megaparsecs (Mpc), the distribution of baryonic and dark matter in the Universe forms the so-called cosmic web. Galaxy clusters serve as the nodes of this intricate structure, and are connected by filamentary chains of galaxies and groups that collectively form galaxy superclusters. In this work, we carried a photometric investigation of the Hydra Super- cluster of galaxies, a large agglomeration of galaxies in the local Universe (z 0.012) composed primarily by the Hydra Cluster (Abell 1060) and its neighbors, such as the Antlia Cluster (Abell S0636). For this, we employ mainly data from the Fourth Data Release of the Southern Pho- tometric Local Universe Survey (S-PLUS DR4), characterized by a 12-filter photometric system that allows for the determination of high-precision photometric redshifts (photo-zs). Our primary objective is to determine galaxy-cluster memberships, enabling us to investigate the properties and evolution of galaxies within these structures. Additionally, this informa- tion aids in the selection of targets for upcoming spectroscopic redshift surveys like CHANCES (CHileAN Cluster galaxy Evolution Survey). Typically, the determination of galaxy member- ships in clusters and other structures relies on spectroscopic redshifts. However, the cost of extensive spectroscopic observations and the absence of a comprehensive survey in the southern hemisphere, comparable to the Sloan Digital Sky Survey (SDSS), has restricted these observa- tions to only the brightest galaxies. To address this limitation, we utilize photometric redshifts to refine membership assignments in the southern hemisphere structures. Our work incorporates the development and implementation of two distinct galaxy-cluster membership methods. The first method employs a sigma-clipping technique, taking into account the typical photo-z uncertainty as a function of galaxy magnitude to identify cluster members. This method has been applied to select targets for observation within the CHANCES Survey. The second method employs a robust Bayesian approach to assign membership probabilities to galaxies in clusters. This approach considers the complete probability density function (PDF) of galaxy photo-z as input. We have successfully tested this method on cluster mocks and applied it to clusters within the Hydra Supercluster region, yielding typical values of purity and completeness of approximately 80%. For the Hydra Cluster, we achieved estimated completeness and purity values of, respectively, 92% and 68% with a 35% membership probability threshold using the second method. Since we are interested in the whole region of Hydra Supercluster, an additional result of our work includes a compilation of 121 groups and clusters of galaxies collected from the literature in the volume of the Supercluster, as well as a search for X-rays sources from the First Data Release of SRG/eROSITA All Sky Survey (eRASS1), that resulted in counterparts at the location of Hydra and Antlia clusters, and a third source associated with NGC 3091, an elliptical galaxy at the northern part of the Supercluster.